Myeloperoxidase induces monocyte migration and activation after acute myocardial infarction - Peters, Vera B.M.; Matheis, Friederike; Erdmann, Immanuel; Nemade, Harshal N.; Muders, David; Toubartz, Martin; Torun, Merve; Mehrkens, Dennis; Geißen, Simon; Nettersheim, Felix Sebastian; Picard, Felix; Guthoff, Henning; et al. (Frontiers in Immunology, 2024)
Myocardial infarction (MI) is a significant contributor to morbidity and mortality worldwide. Many individuals who survive the acute event continue to experience heart failure (HF), with inflammatory and healing processes post-MI playing a pivotal role. Polymorphonuclear neutrophils (PMN) and monocytes infiltrate the infarcted area, where PMN release high amounts of the heme enzyme myeloperoxidase (MPO). MPO has numerous inflammatory properties and MPO plasma levels are correlated with prognosis and severity of MI. While studies have focused on MPO inhibition and controlling PMN infiltration into the infarcted tissue, less is known on MPO’s role in monocyte function. Here, we combined human data with mouse and cell studies to examine the role of MPO on monocyte activation and migration. We revealed a correlation between plasma MPO levels and monocyte activation in a patient study. Using a mouse model of MI, we demonstrated that MPO deficiency led to an increase in splenic monocytes and a decrease in cardiac monocytes compared to wildtype mice (WT). In vitro studies further showed that MPO induces monocyte migration, with upregulation of the chemokine receptor CCR2 and upregulation of inflammatory pathways identified as underlying mechanisms. Taken together, we identify MPO as a pro-inflammatory mediator of splenic monocyte recruitment and activation post-MI and provide mechanistic insight for novel therapeutic strategies after ischemic injury.